Dialogical Approach: Strategies to Prevent Radicalism And Islamophobia in Schools Through Interreligious Dialogue - Azahra, Firda; Muttaqin, Choirul; Ngadhimah, Mambaul (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Radicalism and Islamophobia have increasingly become important issues within educational environments because both influence how students understand religious diversity and interact with individuals from different backgrounds. The absence of constructive social interaction, combined with strong environmental influence and uncontrolled exposure to digital information, often contributes to the development of prejudice from an early age. This research focuses on examining how dialogue-oriented learning can function as an educational strategy to minimize prejudice and strengthen tolerant attitudes among junior high school students. A qualitative case study design was employed to capture students’ experiences and observe interaction patterns occurring in the school environment. Data were gathered through observation, interviews, and supporting documentation, then interpreted through an interactive qualitative analysis process. The findings reveal that students’ perceptions toward religious differences are gradually shaped by family influence, digital media exposure, and limited opportunities for direct interaction with diverse groups. Classroom dialogue activities were found to encourage openness, improve empathy, and help students develop more inclusive perspectives toward diversity. The study highlights the importance of dialogue-based educational practices as an effective effort to reduce intolerance while strengthening multicultural awareness within schools.